Water Reclamation and Reuse. (1st October 2016) - Huang, Chunkai; Zeng, Ping; Yang, Sen; Shao, Yanxi; Liu, Yang
Abstract : A review of the literature published in 2015 on topics relating to water reclamation and reuse is presented. The review is divided into the following sections: (1) General: extent of reuse, research needs, guidelines and monitoring, health effects; (2) Treatment technologies: integrated process design, membrane treatment, membrane bioreactors, electrocoagulation, ion exchange and adsorption, disinfection, wetlands, managed aquifer recharge; (3) Planning and management: public acceptance and education, economics/pricing, water quality planning and management and project/case studies. Much of the water treatment research focuses on membrane treatment, integrated designs, and other innovative technologies.